Queer electronic rave rapping Zulu princesses don’t grow on trees’: a digital ethnography of Toya Delazy’s curated persona as a South African popular musician on Instagram - Friday, Lindsay (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMus)--Stellenbosch University, 2023.